Development of a method for plasma - induced combustion of intermediate to low-level radioactive waste - Nachtrodt, Frederik <1984> (Alma Mater Studiorum - Università di Bologna, 2013)
This work demonstrates that the plasma - induced combustion of intermediate to low-level radioactive waste is a suitable method for volume reduction and stabilization. Weaknesses of existing facilities can be overcome with novel developments. Plasma treatment of LILW has a high economical advantage by volume reduction for storage in final repositories.